Enhancement of Pneumocandin B0 Production in Glarea lozoyensis by Low-Temperature Adaptive Laboratory Evolution - Song, Ping; Zhang, Ke; Zhang, Sen; Huang, Bao-Qi; Ji, Xiao-Jun; Ren, Lu-Jing; Gao, Song; Wen, Jian-Ping; Huang, He (Frontiers in Microbiology, 2018)
The production of pneumocandin B0 is limited by feedback inhibition. Here, low-temperature adaptive laboratory evolution (ALE) was used to improve the production capacity of Glarea lozoyensis by enhancing its membrane permeability. After 50 cycles of ALE, the pneumocandin B0 production of the endpoint strain (ALE50) reached 2131 g/L, which was 32% higher than that of the starting strain (ALE0). ALE50 showed a changed fatty acid composition of the cell membrane, which increased its permeability by 14%, which in turn increased the secretion ratio 3-fold. Furthermore, ALE50 showed increased intracellular proline and acetyl-CoA concentrations, superoxide dismutase and, catalase activity, as well as total antioxidant capacity. The slight biomass decrease in ALE50 was accompanied by enhanced isocitrate dehydrogenase and reduced ATP:citrate lyase activity. Finally, a putative model of the accumulation and secretion of pneumocandin B0 in ALE50 was established. ALE is a promising method to release intracellular feedback inhibition.